Regulation of the JAK2-STAT5 Pathway by Signaling Molecules in the Mammary Gland - Tian, Min; Qi, Yingao; Zhang, Xiaoli; Wu, Zhihui; Chen, Jiaming; Chen, Fang; Guan, Wutai; Zhang, Shihai (Frontiers in Cell and Developmental Biology, 2020)
Janus kinase 2 (JAK2) and signal transducers and activators of transcription 5 (STAT5) are involved in the proliferation, differentiation, and survival of mammary gland epithelial cells. Dysregulation of JAK2-STAT5 activity invariably leads to mammary gland developmental defects and/or diseases, including breast cancer. Proper functioning of the JAK2-STAT5 signaling pathway relies on crosstalk with other signaling pathways (synergistically or antagonistically), which leads to normal biological performance. This review highlights recent progress regarding the critical components of the JAK2-STAT5 pathway and its crosstalk with G-protein coupled receptor (GPCR) signaling, PI3K-Akt signaling, growth factors, inflammatory cytokines, hormone receptors, and cell adhesion.